Fine Characterization Method of Concrete Internal Cracks Based on Borehole Optical Imaging - Chao Wang; Zengqiang Han; Yiteng Wang; Chuanying Wang; Jinchao Wang; Shuangyuan Chen; Sheng Hu (Applied Sciences, 2022)
The internal cracks of concrete are very important in the safety evaluation of structures, but there is a lack of fine characterization methods at present. Borehole cameras are a piece of in situ borehole detection technology which can measure the structural elements of a borehole wall with high precision. In this paper, borehole camera technology is used to measure the concrete cracks of a tunnel floor, and the morphological characteristics (depth, width, and orientation) of the cracks are analyzed. The results show that the average extension depth of the crack extending from the orifice exceeds 1.195 m, and the width decreases with the increase in depth. The crack orientation is basically stable, with the maximum deviation of 19° at the orifice of different boreholes and 30° at different depths of the same borehole. The crack inside the concrete (not extending to the orifice) usually has a small extension depth and a relatively stable width, but the crack orientation changes greatly. The coarse aggregate and concrete interface have different effects on the extension direction of cracks. This paper also conducted a second measurement on two of the boreholes after an interval of 15 days, and found the difference in crack development in the two measurements. The work of this paper provides a new attempt for the detection and monitoring of concrete crack morphology.